Evaluation of Cell Membrane Electropermeabilization by Means of a Nonpermeant Cytotoxic Agent. (May 2000) - Kotnik, Tadej; Maček-Lebar, Alenka; Miklavčič, Damijan; Mir, Lluis M.
For the evaluation of cell membrane electropermeabilization, cells are usually exposed to electric pulses in the presence of propidium iodide, a fluorescent dye activated by binding to cellular DNA. The fraction of permeabilized cells is then determined using a flow cytometer. This widely established method has several drawbacks: (i) an arbitrary choice of minimum fluorescence intensity for characterization of permeabilized cells; (ii) the inability to detect cells disintegrated because of intense electropermeabilization; and (iii) false detection of cellular ghosts devoid of fluorescence because of leakage of DNA caused by electropermeabilization. Here, we present a simple and inexpensive method that eliminates these drawbacks. The method is based on the use of a cytotoxic agent that cannot permeate through an intact plasma membrane and thus leads to selective death of the electropermeabilized cells. The amount of nonpermeabilized cells is then determined by a suitable viability test. Bleomycin at a 5-nM concentration causes no statistically significant effect on cell survival in the absence of electric pulses, yet this concentration is sufficient for lethal toxicity in electropermeabilized cells. The amount of cells surviving the exposure relative to the control gives a reliable value of the fraction of nonpermeabilized cells.